Brazilian consensus for diagnosis, management and treatment of hereditary transthyretin amyloidosis with peripheral neuropathy: second edition - Pinto, Marcus Vinicius; França, Marcondes Cavalcante, Jr; Gonçalves, Marcus Vinicius Magno; Machado-Costa, Marcela Câmara; Freitas, Marcos Raimundo Gomes de; Gondim, Francisco de Assis Aquino; Marrone, Carlo Domenico; Martinez, Alberto Rolim Muro; Moreira, Carolina Lavigne; Nascimento, Osvaldo J. M.; Covaleski, Anna Paula Paranhos; Oliveira, Acary Souza Bulle de; Pupe, Camila Castelo Branco; Rodrigues, Marcia Maria Jardim; Rotta, Francisco Tellechea; Scola, Rosana Herminia; Marques, Wilson, Jr; Waddington-Cruz, Márcia (Arquivos de Neuro-Psiquiatria, 2023)
Hereditary transthyretin amyloidosis with peripheral neuropathy (ATTRv-PN) is an autosomal dominant inherited sensorimotor and autonomic polyneuropathy with over 130 pathogenic variants identified in the TTR gene. Hereditary transthyretin amyloidosis with peripheral neuropathy is a disabling, progressive and life-threatening genetic condition that leads to death in ∼ 10 years if untreated. The prospects for ATTRv-PN have changed in the last decades, as it has become a treatable neuropathy. In addition to liver transplantation, initiated in 1990, there are now at least 3 drugs approved in many countries, including Brazil, and many more are being developed. The first Brazilian consensus on ATTRv-PN was held in the city of Fortaleza, Brazil, in June 2017. Given the new advances in the area over the last 5 years, the Peripheral Neuropathy Scientific Department of the Brazilian Academy of Neurology organized a second edition of the consensus. Each panelist was responsible for reviewing the literature and updating a section of the previous paper. Thereafter, the 18 panelists got together virtually after careful review of the draft, discussed each section of the text, and reached a consensus for the final version of the manuscript.
Keywords: Amyloidosis; Peripheral Nervous System Diseases; Amyloid Neuropathies, Familial